مدى فعالية الحـمـايـة القانونية لحـق الـمـريـض فـي الإعـلام - براهيمي, صفيان (University of Eloued جامعة الوادي, 2022)
حظيت مهنة الطب والأعمال الطبيّة باهتمام قانوني كبير خاصة ما تعلّق بالجانب الإنساني الأخلاقي التي سارعت أغلب التشريعات إلى تنظيمه. وتتعدد التزامات الطبيب إزاء الطبيب سواء من الناحية القانونية أو الأخلاقية بحكم العلاقة المباشرة التي تربطه بالمريض تستدعي منه بذل كل ما في وسعه لإرضاء هذا المريض. من هذا المنطلق فقد نظم التزام الطبيب بالإعلام اتجاه المريض بالنظر الى أهميته في دراية المريض بكل ما يتعلق بحالته الصحية ومن ثم وضع في الحسبان كل الاحتمالات التي قذ تتعلق به في المجال الصحي. وهو ما يبين القيمة القانونية لهذا الالتزام بالإعلام في المجال الصحي خدمة ومساعدة للمريض من جهة وأداء الطبيب لواجبه المهني من جهة أخرى. الكلمات المفتاحية: المريض؛ الحق في الاعلام؛ النصوص القانونية؛ الالتزام. Abstract: The medical profession is the subject of great legal attention, particularly with regard to the human ethical aspect, which most legislation has hastened to regulate. The obligations of the doctor towards the doctor are numerous, whether on the legal or moral level, by virtue of the direct relationship that binds him to the patient, which obliges him to do everything possible to satisfy this patient. From this point of view, the patient's right to information has been regulated taking into account its important role in bringing knowledge to the patient of everything concerning his state of health, and possibly of all the possibilities which may be linked to it. field of health. This shows the legal value of this right to information of the patient in the medical field to assist the patient on the one hand, and on the other hand the fulfillment of the professional duty of the doctor. Keywords : the patient, the right to information, the legal texts, the obligation.
The extent of the effectiveness of the legal protection of the patient's right to information
مقال
Keywords: المريض ; الحق في الإعلام ; النص ; ص القان ; نية ; الالتزام; the patient ; the right to information ; the legal textes ; the obligation